Risk of sarcopenia: A red flag for cognitive decline in postmenopause (2025)
Objective: To determine if the SARC-F tool, used to screen for sarcopenia risk, can also predict mild cognitive impairment (MCI) diagnosed with the Montreal Cognitive Assessment (MoCA) tool. Methods: This is a sub-analysis of data from a cross-sectional study carried out in postmenopausal women from Latin America (nine countries) in which sociodemographic, clinical, and anthropometric data were collected, and the SARC-F and MoCA tools administered. From the original sample of 1185 women, analysis was performed only among the 772 with natural menopause. Results: Overall, mean age, body mass index and years of education were 56.9 years, 26.8 kg/m2 and 13.6 years, respectively. Women with MCI displayed a higher body mass index, had more children, experienced more severe menopausal symptoms, and were more frequently homemakers and physically inactive. The prevalence of MCI increased from 12.9 % in women with no sarcopenia risk (SARC-F < 4 points) to 35.3 % in those at risk (OR 3.70; 95 % CI 2.36–5.80). According to binary logistic regression analysis, sarcopenia risk (total SARC-F score ≥ 4) was associated with MCI (OR: 2.44; 95 % CI 1.50–3.95). Aside from the risk of sarcopenia, being a homemaker (OR 1.97; 95 % CI 1.25–3.10) was also associated with an increased likelihood of MCI. Protective factors included ever use of menopausal hormone therapy (OR 0.26; 95 % CI 0.13–0.54) and having higher educational attainment (OR 0.28; 95 % CI 95 % 0.16–0.47). The SARC-F displayed a sensitivity of 84 % and a specificity of 39 % at diagnosing MCI.